Hypothetical Inquiry Model as a Strategy for Improving Critical Thinking in Elementary School Learning - Ratna Ekawati; Adi Atmoko; Nurul Izhan Pepridel Yulanda (Universitas Pendidikan Ganesha, 2026)
Elementary students’ critical thinking is low due to lecture and memorization based science instruction that limits evidence based reasoning. This study aims to explore the implementation of the hypothetical inquiry model as a strategy for improving fifth-grade elementary school students’ critical thinking skills in science learning, particularly in the topic of simple electricity.This study employed a qualitative approach using a case study design. The hypothetical inquiry model was implemented across five instructional meetings, emphasizing a complete cycle of scientific reasoning, including phenomenon observation, hypothesis formulation, investigative design, data collection and analysis, and hypothesis evaluation. Data were collected through classroom video recordings, participatory observations, in-depth interviews with students, and analysis of students’ learning artifacts. The findings reveal four pedagogical interaction patterns that facilitate the development of students’ critical thinking skills: (1) scaffolding of stepwise hypothesis formulation, (2) collaborative evaluation of evidence through cognitive conflict, (3) construction of evidence-based causal reasoning, and (4) metacognitive reflection on the inquiry process. The students demonstrated progressive improvement in their ability to formulate testable hypotheses, design systematic investigations, and construct evidence-based causal arguments. This study contributes to the inquiry-based learning literature by providing an in-depth description of the pedagogical mechanisms through which the hypothetical inquiry model supports the development of elementary school students’ critical thinking skills in learning abstract science concepts.